Pattern of Breast Diseases among Women Patients Attending Al-Beyda Medical Center - Asma Abdalla; Marfoua Ali; Wedyan Saleh (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. The pathology profile of breast lesions is still not well defined in El-Bayda City of Libya. Breast diseases are a diverse group, with benign neoplasms being the most common lesion. Knowledge of the pattern of such lesions can provide better understanding of their causes, natural history, and preventive strategies. This study was aimed to evaluate the pattern of breast lesions in patients who attended Al-Beyda medical center during Dec 2019 to Dec 2020. Methods. The study was enrolled with (234) women with breast problems. The outline of the breast lesions were tabulated and classified as inflammatory, benign, and malignant, in addition to other lesions like congenital, functional, and developmental ones. Results. The highest prevalence of breast disease was noted in the age groups of 21–40. Mastalgia was the most commonly presented diagnosis with 81% followed by mass palpable with 26% then inflammation 20.9% with significant difference for each lesion in different age groups. Traumatic and idiopathic had the highest percentages of inflammatory lesions (44.89 and 55.3%, respectively). The recurrence of a mass or cyst after intervention is also indicative of inflammatory lesions. Conclusion. The most common breast disorders that women seek medical attention for are breast pain, nipple discharge, and a palpable lump. The majority of women who have these symptoms have benign breast disease